La comunicación digital a través de twitter para el diario La Hora, de la ciudad de Loja - Bravo Villacres, Jhenifer Gabriela (2016)
The topic we investigate in this paper is on digital communication TWITTER THROUGH TIME FOR EVERY DAY OF THE CITY OF LOJA. It should be noted that in order to gather first-hand information, an interview was made the editor of the newspaper La Hora in the province of Loja, yet 100 surveys were conducted at people who read newspaper La Hora, this information can undertake research problem: To what extent influences Twitter digital communication Diario La Hora city of Loja, to their objectives target audiences ?. After the IP, the analysis of the information obtained was performed, which allowed us to develop an alternative proposal. Following the analysis and discussion of the information obtained through the application of tools such as surveys and interviews the editor of the newspaper readers proceeded, which allowed us to formulate conclusions and recommendations. In this way we could realize that Twitter is generally effective means for generating digital communication and used properly meets the inherent human need to be informed.